Glycosylation regulates NK cell-mediated effector function through PI3K pathway - Benson, Veronika; Grobarova, Valika; Richter, Jan; Fiserova, Anna (International immunology, 2010)
Aberrant glycosylation, which impairs recognition capability of NK cells or modifies recognition pattern of target cells, is associated with cancer. Synthetic glycoconjugates (GCs), which modulate cell glycosylation, increase the sensitivity of tumor cells to therapy or boost anti-cancer immune response. In the current study, we employed N-acetyl-D-glucosamine-calix[4]arene (GN4C) as a modulator of cell glycosylation of NK cells represented by the NK-92 cell line and fresh human NK cells. For the first time, we have demonstrated that calix[4]arene-based GC down-regulated the expression of glycosyltransferases MGAT3 and MGAT5 in NK-92 and fresh NK cells. GN4C increased the susceptibility of tumor cells to cytotoxicity by purified fresh NK cells or NK-92 cells. This functional activation of NK cells and the NK-92 cell line correlated with an increased expression of NKG2D mRNA. In the NK-92 cell line, GN4C induced the synthesis of IL-2, IFN-gamma and tumor necrosis factor-alpha as well. Cellular signaling triggered by GN4C engaged PI3-kinase/ERK but not phospholipase C-gamma/JNK pathways. Simultaneously, in transformed NK-92 cells, GN4C reduced the rate of proliferation and down-regulated the c-MYC, EGF-receptor 1 and REL-A molecules. In conclusion, the modulation of glycosyltransferases MGAT3 and MGAT5 by synthetic GN4C correlated with the improvement of NK cell effector functions and the augmentation of tumor cells sensitivity to NK cell-mediated cytotoxicity.
Keywords: fosfatidylinositol-3-kinasy; buňky HT-29; Gene Expression Regulation, Neoplastic; exprese genu; Gene Expression; RNA, Messenger; Cell Line; Cytotoxicity, Immunologic; Neoplasms; Cell Proliferation; separace buněk; acyltransferasy; regulace genové exprese u nádorů; glykokonjugáty; signální transdukce; proteiny nervové tkáně; Lymphocyte Activation; Phosphatidylinositol 3-Kinases; Glycoconjugates; polymerázová řetězová reakce s reverzní transkripcí; Flow Cytometry; cytotoxicita imunologická; Oligonucleotide Array Sequence Analysis; Signal Transduction; aktivace lymfocytů; průtoková cytometrie; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; lidé; Acyltransferases; Cell Separation; N-Acetylglucosaminyltransferases; Humans; buňky NK; HT29 Cells; Reverse Transcriptase Polymerase Chain Reaction; buněčné linie; proliferace buněk; nádory; glykosylace; Glycosylation; Killer Cells, Natural; N-acetylglukosaminyltransferasy; messenger RNA; Nerve Tissue Proteins